A Combination of Hill Cipher and LSB for Image Security - Mulyono, Ibnu Utomo Wahyu; Susanto, Ajib; Febrian, Muhamad Rizky Fajar; Rosyida, Ghaitsa Ardelia (Scientific Journal of Informatics, 2020)
The maximum value obtained to test the encrypt hill cipher uses the avalanche effect with modification of one, two, three, and four key matrices 35.71%, therefore an additional security technique is needed. The Least Significant Bit (LSB) method is used to insert the ciphertext that has been generated from the hill cipher algorithm, has been testing using RGB, CMY, CMYK and YUV shapes with 6142 characters in 128 x 128 character images producing the highest PSNR value of 51.2826 dB in CMYK images. Steganography technique is applied because it has advantages in terms of imperceptibility, for example the results of a stego image are so similar to the original image that it is difficult to be distinguished by the human senses. Tests were carried out with 10 images, five images measuring 512 x 512 and five images measuring 16 x 16. While the messages to be inserted were 240, 480, and 960 characters for images measuring 512 x 512 and 24, 48 and 88 characters for images measuring 16 x16. Test results that I have done are calculated using Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR) with a minimum PSNR of 51.2907 dB which means the resulting image is quite good. Computation time is calculated using tic toc on Matlab by encrypting 2000 and 6000 characters, and also computation time.